2014
DOI: 10.2460/javma.245.11.1251
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of ovarian remnant syndrome in dogs and cats: 7 cases (2010–2013)

Abstract: Laparoscopic management of ORS in this cohort of dogs and cats was associated with minimal morbidity. Laparoscopic treatment of ORS in dogs and cats may be recommended for appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
2
27
1
1
Order By: Relevance
“…In the limited number of cases presented here, neither surgical nor postsurgical complications were encountered. Results of this study were similar to a report by Naiman et al () that reported successful treatment of ovarian remnant syndrome in five dogs and two cats, with similar results to those reported here. Further prospective evaluation of the laparoscopic technique would be required to compare intraoperative and postoperative outcomes with coeliotomy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the limited number of cases presented here, neither surgical nor postsurgical complications were encountered. Results of this study were similar to a report by Naiman et al () that reported successful treatment of ovarian remnant syndrome in five dogs and two cats, with similar results to those reported here. Further prospective evaluation of the laparoscopic technique would be required to compare intraoperative and postoperative outcomes with coeliotomy.…”
Section: Discussionsupporting
confidence: 92%
“…In the limited number of cases presented here, neither surgical nor postsurgical complications were encountered. Results of this study were similar to a report by Naiman et al (2014) that reported successful treatment of ovarian remnant syndrome in five dogs and two cats, with similar results to those reported here.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, applications in the veterinary field have not yet been so widely attempted or established. It has only been within the last 10 to 15 years that minimally invasive techniques have been considered for application in veterinary surgery (Case, Marvel, Boscan, & Monnet, 2011;Dupré et al, 2009;Mayhew, Mehler, & Radhakrishnan, 2008;Naan, Kirpensteijn, Dupre, Galac, & Radlinsky, 2013), particularly in the field of animal reproduction (Adamovich-Rippe et al, 2013;Becher, Aurich, & Dupré, 2014;Dupré et al, 2009;Naiman et al, 2014;Swanson, 2012).…”
Section: Advances In Endoscopic Surgery For Small Animal Reproductionmentioning
confidence: 99%
“…The best way for treatment is removing the residual ovarian tissue through diagnostic laparotomy or laparoscopic surgery (Naiman, 2014;Phipps, 2015 residual tissue by radiography and ultrasonography in this case because by this medicine the amount of tissue is diminished (Sontas et al, 2007;Ball et al, 2010). On the other hand, there were no great blood vessels on the surface of the found residual tissue, which was favored by the action of the medicine to avoid complications as intrasurgical bleeding (Sontas et al, 2007).…”
Section: Fig 1 Radiology In Ventro-dorsal View -Without Visual Pathmentioning
confidence: 99%